Identification of core components and implementation strategies for a Conservative Kidney Management Pathway across a complex, multisector healthcare system in Canada using World Cafés and the Theoretical Domains Framework - Jayna Holroyd-Leduc; Sara Davison; Vanessa Steinke; Betty Ann Wasylynuk (BMJ Open)
Objective Develop a Conservative Kidney Management (CKM) Pathway for patients unlikely to benefit from dialysis. We sought to determine (1) core components of care and (2) implementation strategies across a multisector healthcare system.Design We used the Knowledge to Action Cycle and the Theoretical Domains Framework to identify barriers and facilitators to CKM. Activities included a current state assessment, World Cafés, interviews, focus groups and readiness for change assessments.Setting A provincial initiative in Alberta, Canada.Participants 282 participants were purposively selected to reflect those involved in the care of patients receiving CKM. This included policy-makers, multidisciplinary healthcare professionals, patients and their family.Main outcome measures Theoretical domains linked to pathway content and implementation strategies.Results Environmental context and resources, social/professional role and identity, knowledge and social influences were the most influential behaviour change domains identified. The most effective strategies for facilitating behaviour change were identified to be education, training, environmental restructuring and modelling. Core components of care were determined to be guidelines for treating symptoms and disease complications consistent with the philosophy of CKM, timely communication of the choice for CKM, coordination with community services, crisis planning, advance care planning and tools to enhance patients’ capacity for self-management and shared decision-making. This resulted in development of Alberta’s CKM Pathway, an interactive, digital, decision-support tool consisting of: (1) a patient decision aid; (2) a patient/family portal; and (3) a healthcare professional portal, where all resources can be freely accessed.Conclusions The pathway was codesigned by patients and healthcare professionals and involves tailor-made combinations of tools to address unique patient needs and system-community circumstances. Most of the strategies are adaptable to local context and are likely translatable to the implementation of sustainable CKM in other national and international jurisdictions.